Diagnostic Efficacy of 2-D Elastography for Liver Fibrosis in Subjects with Viral Hepatitis - Tahir, Muhammad Masood; Farooqui, Umair; Manzoor, Aqsa (Biological and Clinical Sciences Research Journal, 2025)
Chronic hepatitis C virus (HCV) infection is a leading cause of liver fibrosis and cirrhosis worldwide. Early and accurate staging of liver fibrosis is critical for clinical decision-making and prognostication. While liver biopsy remains the gold standard, non-invasive modalities like two-dimensional shear wave elastography (2D SWE) are gaining attention due to their reproducibility, patient comfort, and diagnostic efficiency. Objective: To evaluate the diagnostic utility of 2D shear wave elastography for diagnosis of liver fibrosis in HCV patients with chronic liver disease. Methods: A prospective analysis was conducted on adult 200 HCV patients in the Medicine Department of Nishtar Hospital, Mulan from March 2024 to March 2025. The patients with chronic liver disease undergoing SWE and liver biopsy were selected for the study. All patients underwent two-dimensional SWE in a supine position by two independent radiologists and liver biopsy was performed in the same posture and same session as SWE. Laboratory tests were performed and biomarker indices were calculated. Results: Spearman’s rank tests showed that shear wave velocity was significantly associated with total bilirubin (0.245), AST (0.522), ALT (0.387), albumin (-0.478), prothrombin time (0.413), platelet count (0.413), hyaluronic acid (0.702) and type IV collagen 7S (0.729), M2BPGi (0.705). The AUC of SWE for cirrhosis was 0.952 (95% CI: 0.89-0.95), for hyaluronic acid was 0.860, type IV collagen 7S was 0.872, M2BPGi was 0.879, AST to platelet ratio index was 0.892 and Fibrosis-4 index was 0.896. Conclusion: The 2D SWE showed a high accuracy for predicting fibrosis grades and severity as compared to other biomarkers in HCV patients.